S64 Eosinophil Cationic Protein And Cytokine Analysis In Exhaled Breath Condensate In Paediatric Asthma. (10th November 2014) - Whitehouse, A; Brugha, R; Mushtaq, N; Dundas, I; Grigg, J
Abstract : Background: Sputum eosinophil counts are unstable in childhood asthma. 1 This makes sputum induction to quantify sputum eosinophils an unsuitable test to guide anti-inflammatory therapy. 2 While eosinophils may be cleared following apoptosis, free eosinophil granules, containing effector proteins, may persist in the airway lumen. We speculated that inflammatory mediators in exhaled breath condensate, released by eosinophils (such as eosinophil cationic protein (ECP)) could aid risk-profiling in children with asthma. We therefore sought to assess whether ECP is present in EBC from asthmatic children, alongside an assessment of pro-inflammatory cytokines. Methods: Children with asthma aged 7–15 and age matched healthy controls underwent spirometry, sputum induction, collection exhaled breath condensate (EBC), and completed the childhood asthma control test. Exhaled breath was tested for eosinophil cationic protein (ECP) using an immunoassay. A cytokine analysis of the exhaled breath condensate was also carried out in addition to a sputum leucocyte differential. Exhaled breath condensate (EBC) was collected in an R-tube following manufacturer protocol, over 10 min. Results: Sputum leucocyte counts were performed in 33 children with asthma. Suitable samples (visible airway plugs) were obtained from 14 children at baseline who concurrently provided EBC samples. Of these, 7/14 (50%) were eosinophilic and 7/14 (50%) were non-eosinophilic. The cytokine analysis showed that IL-4 did not differ between groups. IL-13 was raised in children who had sputum eosinophilia (2.54 ± 1.18 vs. 0.87 ± 1.49 pg/ml, mean±sd, p = 0.0387, unpaired t-test). Exhaled breath condensate was collected in 26 asthmatic children and 10 controls. ECP was detected in EBC from 5/26 asthmatic children and 0/10 healthy children. In 2 asthmatic children, detectable ECP was associated with sputum eosinophilia (>2.5%). In one child ECP was detectable with no induced sputum eosinophils. (Table 1 ). Discussion: ECP may be identified in EBC from children with asthma, and is not exclusively associated with concurrent sputum eosinophilia. Eosinophilia may be identified non-invasively by measuring Th2 cytokines in EBC. These techniques may provide additional insights into underlying airway inflammation and identify children who may benefit from specific anti-Th2 cytokine monoclonal antibody therapies. References: Fleming L, Tsartsali L, Wilson N, Regamey N, Bush A. Sputum inflammatory phenotypes are not stable in children with asthma. Thorax 2012; 67: 675–681 Fleming L, Wilson N, Regamey N, Bush A. Use of sputum eosinophil counts to guide management in children with severe asthma. Thorax 2012; 67: 193–198